(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Jedną z przesłanek, za pomocą której można modyfikować dolegliwość sankcji odszkodowawczej jest określenie stopnia winy, która jest istotna nie tylko z punktu widzenia prawa karnego ale także prawa cywilnego. Autor artykułu przedstawia zagadnienie gradacji winy i jej związku ze społeczno-gospodarczymi funkcjami odpowiedzialności cywilnej, wskazuje na szczególne znaczenie gradacji winy dla represyjnej funkcji odpowiedzialności cywilnej. Charakteryzuje trzy typowe stopnie winy oraz jej ewentualne dalsze stopniowanie. Rozważania wzbogaca o zagadnienia jedności pojęcia winy w prawie cywilnym jak i karnym, Ponadto opisuje pojęcia winy umyślnej, rażącego niedbalstwa oraz niedbalstwa. One of the prerequisites by means of which the severity of the compensation sanction can be modified is the determination of the degree of fault, which is relevant not only from the point of view of criminal law but also civil law. The author of the article presents the issue of the gradation of fault and its relation to the socio-economic functions of civil liability, and points out the particular importance of the gradation of fault for the repressive function of civil liability. He characterises three typical degrees of guilt and its possible further gradation. The discussion is enriched by the issue of the unity of the concept of fault in civil as well as criminal law. Furthermore, he describes the concepts of intentional fault, gross negligence and negligence.